A novel mutation in RS1 and clinical manifestations in a Chinese twin family with congenital retinoschisis - Wang, Xiao-Fang; Chen, Fei-Fei; Zhou, Xin; Cheng, Xin-Xuan; Xie, Zheng-Gao (Frontiers in Genetics, 2022)
Purpose We aim to analyze the clinical and genetic features in a Chinese family with congenital retinoschisis by whole-exon sequencing and comprehensive clinical examination. Methods 6 members were recruited from a Chinese family, and 3 of them were diagnosed as congenital retinoschisis including 2 twin siblings. All subjects received a full eye examination. Whole-exome sequencing (WES) and Sanger sequencing were performed on two twin probands and all participants respectively. Results A novel splice site mutation RS1.c.53-1G>A was identified in a Chinese congenital retinoschisis family. The mean onset age was 16.7±2.4 years old. The average BCVA in patients was 0.37±0.05. A typical spoke-wheel pattern was observed in all the affected eyes. OCT examination results showed fovea schisis and schisis cavities were located in the inner nuclear layer in 100% eyes (6/6). ERG b/a ratio was decreased markedly, but still more than 1 in four eyes available. Conclusions the present study discovered a new pathogenic splice cite variant of RS1 in congenital retinoschisis, expanding the mutational spectrum. Different to previous researches, phenotype of patients with the same mutation within one family was highly similar. Early molecular testing is crucial for early diagnosis, clinical management and genetic counselling of patients with congenital retinoschisis. Key words congenital retinoschisis, gene mutation, RS1, sequencing,